Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Direction of A Curve

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 7

direction of a curve

Exercise 1

Find the equation of the tangent line and the normals of the curve at the points indicated
y=tan 2 x at the point (0.0)

We calculate the derivative of the function:

y=tan 2 x

2 d
f ℩ ( x )=sec 2 x (2 x )
dx
2
f ℩ ( x )=2 sec 2 x

We calculate the derivative at the point to obtain the slope of the tangent line:

dy
m= (0 , 0)
dx
2
m=2 sec 2(0)

m=2(1) ⟹ m=2

In this case we already have the slope of the tangent line and the point, finally we have to
calculate the equation of the line using the formula:

Y −Yo=m∗( X− Xo)

Y −0=2( X−0)

y=2 x

−1
To calculate the normal line, proceed with the formula: m 2= which tells us that the
m1
normal line is perpendicular to the tangent line

−1
m 2=
m1

−1
m 2=
2
In this case we already have the slope of the normal line and the point, finally we have to
calculate the equation of the line using the formula:

Y −Yo=m∗( X− Xo)

−1
Y −0= (X−0)
2

−1
y= x
2

2 y=−x

−x
y=
2

Exercise 2

Find the equation of the tangent line and the normals of the curve at the points indicated
4 4
y =4 x +6 xy at the point (1,2)

We calculate the derivative of the function:

4 4
y =4 x +6 xy

3 ¬ 3 dy dy
f ℩ ( x )=4 y y =16 x +(6 x y + y 6 x)
dx dx
3 ¬ 3 ¬
4 y y =16 x +6 x y +6 y
3 ¬ ¬ 3
4 y y −6 x y =6 y+ 16 x

y ¬ ( 4 y 3−6 x ) =6 y +16 x 3
2
3 y +8 x
y= 2
2 y −3 x
We calculate the derivative at the point to obtain the slope of the tangent line:

dy
m= (1 ,2)
dx

3(2)+8(1)
m=
2(2)−3(1)

14
m=
13

In this case we already have the slope of the tangent line and the point, finally we have to
calculate the equation of the line using the formula:

Y −Yo=m∗( X− Xo)

14
Y −2= (X −1)
13

13 ( y−2 ) =14 ( x−1 )

13 y−26=14 x−14

14 x−12
y=
13

−1
To calculate the normal line, proceed with the formula: m 2= which tells us that the
m1
normal line is perpendicular to the tangent line

−1
m 2=
m1

1

1
m 2=
14
13

−13
m 2=
14
In this case we already have the slope of the normal line and the point, finally we have to
calculate the equation of the line using the formula:

Y −Yo=m∗( X− Xo)

−13
Y −2= ( X−1)
14

14 ( y −2 )=−13(x −1)

14 y −28=−13 x +13

14 y =−13 x + 41

−13 x +41
y=
14

Exercise 3

Find the equation of the tangent line and the normals of the curve at the points indicated
2 2
x −xy + y =7 at the point (-1,2)

We calculate the derivative of the function:

2 2
x −xy + y =7

(
f ℩ ( x )=2 x− x
dy
dx
y+ y
dy
dx )
+2 y y ¬ =7

¬ ¬
2 x−x y − y +2 y y =0
¬ ¬
2 y y −x y =−2 x + y
¬
y ( 2 y−x )=−2 x + y

−2 x+ y
y=
2 y−x

We calculate the derivative at the point to obtain the slope of the tangent line:
dy
m= (−1 ,2)
dx

−2(−1)+(2)
m=
2(2)−(−1)

4
m=
5

In this case we already have the slope of the tangent line and the point, finally we have to
calculate the equation of the line using the formula:

Y −Yo=m∗( X− Xo)

4
Y −2= ¿
5

4
Y −2= ( X +1)
5

5 ( y−2 ) =4 ( x +1 )

5 y−10=4 x + 4

4 x+14
y=
5

−1
To calculate the normal line, proceed with the formula: m 2= which tells us that the
m1
normal line is perpendicular to the tangent line

−1
m 2=
m1

1

1
m 2=
4
5
−5
m 2=
4

In this case we already have the slope of the normal line and the point, finally we have to
calculate the equation of the line using the formula:

Y −Yo=m∗( X− Xo)

−5
Y −2= X −(−1)
4

−5
Y −2= ( X +1)
4

4 ( y −2)=−5( X +1)

4 y−8=−5 X−5 ¿

−5 x +3
y=
4

Exercise 4

Find the equation of the tangent line and the normal line of the curve y=x 3 +1 at the
abscissa point 1.

We apply the straight line formula to obtain the slope

Y −Yo=m∗−( X− Xo)

P( Xo, Yo)

We calculate the variable and replacing the abscissa data

3
f ( x)=x +1
3
f (1)=1 + 1

y=2

P(1 , 2)

We differentiate the function to obtain the slope

3
f ( x)=x +1

2
f ℩ (x )=3 x -

2
f ℩ (x )=3(1)

f ℩ (x )=3

m=3

In this case we already have the slope of the tangent line and the point, finally we have to
calculate the equation of the line using the formula:

Y −Yo=m∗( X− Xo)

Y −2=3∗( X−1)

Y =3 x−3+ 2

Y =3 x−1

You might also like